This [Black] Woman’s Work: Exploring Archival Projects that Embrace the Identity of the Memory Worker - Powell, Chaitra; Smith, Holly; Murrain, Shaneé; Hearn, Skyla (KULA, 2018)
Archivists who work on African American collections are increasingly more aware that traditional sites of African American agency and autonomy are becoming more unstable. The need to capture the perspectives and histories of these institutions is urgent. The challenges become more acute when communities recognize the need to preserve their legacies but do not have the resources or support to make it happen. African American material culture and history remains at risk of co-optation from large institutions and individuals seeking to monetize and profit from collecting Black collections. Endemic in that process is the risk of these institutions controlling the narrative and inadvertently or deliberately erasing the narratives of these diverse communities from that community’s perspective. Cultural memory workers focused on African American collections face numerous challenges: the risk of losing the materials or communities themselves; partnering with organizations and administrations with differing, and perhaps conflicting agendas; working on projects with limited or term funding; and the emotional labor of being a person of color in a predominantly white field trying to support communities that can often reflect their own experiences. How can libraries, museums, and archives bring these communities into the world of archives and empower them to protect and share their stories? How can archivists, particularly those of color, find support within their institutions and the archival profession, to accomplish this work of preserving African American cultural heritage? How can archives support genuinely collaborative projects with diverse Black communities without co-opting their stories and collections?The authors will address these questions in this article, discussing their experiences working with a variety of institutions—predominantly white universities, Black colleges, churches, neighborhoods and families. The authors also include their reflections from their National Conference of African American Librarians panel presentation in August 2017 on these related topics.